Eksplorasi Pengalaman Orang Tua terhadap Persiapan Kerja Individu dengan Disabilitas - Marshalena Chandra; Erayanti Saloko (Jurnal Terapi Wicara dan Bahasa, 2026)
Backgroud: Although employment participation among individuals with disabilities remains low, little is known about how parents prepare their children for employment in the Indonesian context.. This is influenced by limited opportunities from companies and the role of parents in work preparation. Objectives: This study aims to explore the experiences and perspectives of parents regarding work preparation for individuals with disabilities in a phenomenological context, using several population criteria in several cities in Java. Methods: This study is a qualitative phenomenological study. Data were collected through semi-structured interviews with eight parents of individuals with disabilities, obtained through accidental sampling. Data were analyzed using thematic analysis. Results: This study yielded three main themes: (1) Parents' perspectives influence the hopes and beliefs in work preparation of individuals with disabilities, (2) Parental participation in supporting the work preparation of individuals with disabilities, and (3) Challenges faced by parents in the work preparation of individuals with disabilities. Conclusion: The results of the study indicate that parental perspectives play a significant role in shaping the work readiness of individuals with disabilities. Parents actively participate in the process through skill development, emotional support, and collaboration with professionals. Furthermore, parents face several challenges, such as concerns about individual limitations, limited access to information, and the support systems needed to prepare individuals to enter the workforce. Keywords: Individuals With Disabilities, Work Preparation, Parental Perspectives.